2014
DOI: 10.1002/rra.2813
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Modelling to Assess Hydrological Impacts and Evaluate Environmental Flow Scenarios in Montane River Systems Regulated for Hydropower

Abstract: To improve understanding of natural and managed flow regimes in data‐sparse regulated river systems in montane areas, the commonly used Hydrologiska Byråns Vattenbalansavdelning (HBV) conceptual run‐off model was adapted to incorporate water regulation components. The extended model was then applied to the heavily regulated river Lyon (391 km2) in Scotland to reconstruct the natural flow regime and to assess the impacts of regulation at increasing spatial scales. Multi‐criteria model evaluation demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…It is assumed that all barriers are fully passable in the downstream direction. Further details of the Tay and Lyon catchment areas and regulation schemes are reported by Birkel et al (), Geris et al (), and Soulsby et al ().…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is assumed that all barriers are fully passable in the downstream direction. Further details of the Tay and Lyon catchment areas and regulation schemes are reported by Birkel et al (), Geris et al (), and Soulsby et al ().…”
Section: Methodsmentioning
confidence: 97%
“…Owing to its glacial history, the catchment has steep hillslopes and tributary streams, with a wide gently sloping valley bottom. Hydropower infrastructure was developed in the 1950s; since then, the river has been heavily regulated for hydropower (Geris et al, ; Soulsby, Birkel, Geris, & Tetzlaff, ), and so, in addition to natural semi‐passable barriers (i.e., waterfalls that are passable under certain conditions), there are a number of manmade barriers to fish migration (i.e., dams; Figure a). Passability of barriers is based on the Scottish Environmental Protection Agency dataset on barriers to fish migration (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…There are common features among conceptual hydrological models as demonstrated by PDM (Moore, 2007), ARNO (Todini, 1996), HBV (Geris et al, 2014), and Xinanjiang (XAJ) (Zhao, 1980;1992;Zhao and Liu, 1995), such as using multi-bucket concepts, and unrealistic modelling of their soil moisture (e.g., their maximum soil moisture is set at the field capacity).…”
Section: Xaj Hydrological Modelmentioning
confidence: 99%
“…Their results indicated that human activities, such as the expansion of agricultural areas, dam construction, and industrial activities, were responsible for more than 50% of the streamflow reduction in the basin (Wang et al, 2013). Geris et al (2015) employed the HBV model to investigate the flow regime variation (i.e., magnitude, frequency, and duration) in a highly regulated catchment in the River Lyon, Scotland. The aim was to develop a model applicable to highly regulated areas and data-sparse regions.…”
mentioning
confidence: 99%
“…The aim was to develop a model applicable to highly regulated areas and data-sparse regions. The results indicated that the flow regime had reduced in magnitude, frequency, and duration, at both inter-and intra-annual scales, due to regulation activities in the catchment (Geris et al, 2015). In a study conducted by Birhanu et al (2019), the HBV model was applied to the Gumara catchment's water system in Ethiopia to assess the impact of land use and land cover change on the water cycle and, more specifically, streamflow variation.…”
mentioning
confidence: 99%